Discovery of the subgenus Lithobius (Sigibius) Chamberlin, 1913 (Chilopoda: Lithobiomorpha: Lithobiidae) in East Asia: A review the Chinese species - Ma, Huiqin; Pei, Sujian; Li, Yaying; Shi, Baojun (Zootaxa, 2012)
The present paper reviews the centipede species of the subgenus Lithobius (Sigibius) Chamberlin, 1913 (Lithobiomorpha: Lith-obiidae) of the Chinese fauna, including a new species Lithobius (Sigibius) trichinocaput sp. n. recently discovered from HebeiProvince, the only East Asian record of this otherwise Central and North America subgenus of Lithobiomorpha. Diagnoses ofthe subgenus and the species, detailed account on species distribution and a key to the Chinese Lithobius (Sigibius) species are presented.